About one-half of early spontaneous preterm deliveries can be identified by a rapid matrix metalloproteinase-8 (MMP-8) bedside test at the time of mid-trimester genetic amniocentesis*. (2nd August 2016) - Kim, Sun Min; Romero, Roberto; Lee, JoonHo; Chaemsaithong, Piya; Lee, Min-Woo; Chaiyasit, Noppadol; Lee, Hyo-Jin; Yoon, Bo Hyun
Abstract: Objective : Mid-trimester amniocentesis continues to be used for the prenatal diagnosis of chromosomal anomalies and other genetic disorders. Analysis of amniotic fluid obtained at the time of mid-trimester genetic amniocentesis identifies those patients who are at risk for early spontaneous preterm delivery. This is based on a solid body of evidence that found subclinical intra-amniotic inflammation/infection to be causally linked to early spontaneous preterm birth. Although several biomarkers have been proposed to identify intra-amniotic inflammation, the accumulated data suggest that the determination of amniotic fluid matrix metalloproteinase-8 (MMP-8), or neutrophil collagenase, is a powerful predictor of spontaneous preterm delivery. MMP-8 is released by inflammatory cells in response to microbial products or "danger signals". A rapid point-of-care test has been developed to determine MMP-8 at the bedside within 20 min, and without the requirement of laboratory equipment. The objective of this study was to determine whether an elevation of MMP-8 in the amniotic fluid, measured by a rapid point-of-care test, can identify those patients at risk for spontaneous preterm delivery after a mid-trimester genetic amniocentesis. Study design : A case–control study was designed to obtain amniotic fluid from asymptomatic singleton pregnant women who underwent mid-trimester genetic amniocentesis. An MMP-8 bedside test was performed to analyze the amniotic fluid of 64 patients with early spontaneous preterm delivery (<30 weeks) and 128 matched controls with normal pregnancy outcomes. Results : (1) The MMP-8 bedside test (Yoon's MMP-8 Check™) was positive in 42.2% (27/64) of patients with spontaneous preterm delivery but in none (0/128) of the control cases ( p  < 0.001); (2) the MMP-8 bedside test had a sensitivity of 42.2%, and a specificity of 100% in the prediction of spontaneous preterm delivery (<30 weeks) following a mid-trimester genetic amniocentesis; and (3) among the patients with spontaneous preterm delivery, those with a positive MMP-8 bedside test had a significantly higher rate of spontaneous delivery within 2 weeks and 4 weeks of an amniocentesis [40.7% (11/27) versus 5.4% (2/37); 63.0% (17/27) versus 24.3% (9/37)] and a shorter interval-to-delivery period than those with a negative test [interval-to-delivery: median (range), 16 d (0–95 d) versus 42 d (2–91 d); p  < 0.05 for each]. Conclusion : We conclude that 42% of patients with an early spontaneous preterm delivery (< 30 weeks) could be identified by a rapid MMP-8 bedside test at the time of their mid-trimester genetic amniocentesis. The MMP-8 bedside test is a powerful predictor of early spontaneous preterm birth in asymptomatic pregnant women.